Helicobacter pylori-Induced Heparanase Promotes H. pylori Colonization and Gastritis - Tang, Li; Tang, Bo; Lei, Yuanyuan; Yang, Min; Wang, Sumin; Hu, Shiping; Xie, Zhuo; Liu, Yaojiang; Vlodavsky, Israel; Yang, Shiming (Frontiers in Immunology, 2021)
Chronic gastritis caused by helicobacter pylori (H. pylori) infection has been widely recognized as the most important risk factor for gastric cancer. Analysis of the interaction between the key participants in gastric mucosal immunity and H. pylori infection is expected to provide important insights for the treatment of chronic gastritis and the prevention of gastric cancer. Heparanase is an endoglycosidase that degrades heparan sulfate, resulting in remodeling of the extracellular matrix thereby facilitating the extravasation and migration of immune cells towards sites of inflammation. Heparanase also releases heparan sulfate-bound cytokines and chemokines that further promote directed motility and recruitment of immune cells. Heparanase is highly expressed in a variety of inflammatory conditions and diseases, but its role in chronic gastritis has not been sufficiently explored. In this study, we report that H. pylori infection promotes up-regulation of heparanase in gastritis, which in turn facilitates the colonization of H. pylori in the gastric mucosa, thereby aggravating gastritis. By sustaining continuous activation, polarization and recruitment of macrophages that supply pro-inflammatory and pro-tumorigenic cytokines (i.e., IL-1, IL-6, IL-1β, TNF-α, MIP-2, iNOS), heparanase participates in the generation of a vicious circle, driven by enhanced NFκB and p38-MAPK signaling, that supports the development and progression of gastric cancer. These results suggest that inhibition of heparanase may block this self-sustaining cycle, and thereby reduce the risk of gastritis and gastric cancer.